Seismic analysis of dam-relevant structures in Northern Thailand - Bhuddarak Charatpangoon (2020)
©Int. J. of GEOMATE. The damages and losses caused by dam failure are significant. Currently, the seismic safety of dams is well established. However, a study concerning the seismic safety of dam-relevant structures is necessary. Occasionally, dams may withstand an earthquake; however, they are often unable to operate after the quake due to malfunctioning dam-relevant structures.Furthermore, the collapse of such structures could lead to a dam failure or cause considerable losses to the society downstream as well. Therefore, the seismic safety of dam-relevant structures cannot be neglected, and such safety precautions must be conducted properly. The main goal of this research is to evaluate the seismic safety of a dam spillway in Northern Thailand and to ensure that it can operate normally after an expected large earthquake. First, a representative dam-relevant structure is selected based on the availability of data and its importance. Afterward, the performance goal of a representative structure will be established upon its importance, expected performance, and ground motion level. For example, all structural components must be intact, and the uncontrollable release of reservoir water must not take place during and after the maximum considered earthquake (MCE). The seismic analysis of a representative structure is then performed using a numerical simulation. Finally, based on the results, suggestions are made regarding the seismic safety of the representative structure.